Mapping the feel of the arm with the sight of the object: on the embodied origins of infant reaching - Corbetta, Daniela; Thurman, Sabrina L.; Wiener, Rebecca F.; Guan, Yu; Williams, Joshua L. (Frontiers in Psychology, 2014)
For decades, the emergence and progression of infant reaching was assumed to be largely under the control of vision. More recently, however, the guiding role of vision in the emergence of reaching has been downplayed. Studies found that young infants can reach in the dark without seeing their hand and that corrections in infants’ initial hand trajectories are not the result of visual guidance of the hand, but rather the product of poor movement speed calibration to the goal. As a result, it has been proposed that learning to reach is an embodied process requiring infants to explore proprioceptively different movement solutions, before they can accurately map their actions onto the intended goal. Such an account, however, could still assume a preponderant (or prospective) role of vision, where the movement is being monitored with the scope of approximating a future goal-location defined visually. At reach onset, it is unknown if infants map their action onto their vision, vision onto their action, or both. To examine how infants learn to map the feel of their hand with the sight of the object, we tracked the object-directed looking behavior (via eye-tracking) of three infants followed weekly over an 11-week period throughout the transition to reaching. We also examined where they contacted the object. We find that with some objects, infants do not learn to align their reach to where they look, but rather learn to align their look to where they reach. We propose that the emergence of reaching is the product of a deeply embodied process, in which infants first learn how to direct their movement in space using proprioceptive and haptic feedback from self-produced movement contingencies with the environment. As they do so, they learn to map visual attention onto these bodily centered experiences, not the reverse. We suggest that this early visuo-motor mapping is critical for the formation of visually-elicited, prospective movement control.